EFFECT OF USING LOCAL UNTREATED BLACK BARLEY OR TREATED WITH B-GLUCANASE ENZYME OR GERMINATED INSTEAD OF YELLOW CRON IN LAYING HENS NUTRITION - Ibrahim Said Ibrahim (Mesopotamia Journal of Agriculture)
This study was conducted in the fields of the College of Veterinary Medicine / Mosul University , for five months duration . A total of 210 hens (Hubbard breed) were distributed in seven treatments (two rep. / treat). the experimental treat . consist of the control (0٪ barley+ 60٪ corn), 30٪ untr. or treat with -glucanase enzyme or germinated barley , 60٪ untr. or treat with -glucanase or germinated barley. The results showed a significant increase (p ≥ 0.05) in HD٪ egg production , egg weight , total egg mass per hen and feed conversion efficiency in birds fed the diet containing 30 ٪ barley treat with. -glucanase with the same level of yellow corn. No significant effect were showed in feed consumption between the control diet and others containing 30 or 60 ٪ barely treated with -glucanase or germinated . the results was revealed also a significant increase in the percent of blood and meat spots in the eggs of the treats . containing 60 ٪ corn or 30 ٪ corn with the same level of barley. The concentration of cholesterol in egg youlk and blood serum were decreased in all diets containing 60٪ barley.